Exploring Implicit Corrective Feedback Preferences on Students’ Speaking Performance - Rozak, Diana Rahmawati; Maisa, Maisa; Hartati, Sri (Linguistics and ELT Journal, 2023)
The purpose of this study is to explore the students’ preferences and perceptions toward implicit corrective feedback on their speaking performance. This research is qualitative case study research with data collection techniques using observation, questionnaires, and interviews. The participants of this study were 12th-grade, high school students. The author found the most preferred types and timing in the corrective feedback implementation such as: Recast CF, and Immediate CF as the method to correct the errors in their speaking performance given by the teacher. Researchers also found that students have positive perceptions toward implicit corrective feedback. Most participants prefer to be corrected by their teacher when they make an error in their speaking performance.